Acceleration of lipid oxidation in raw stored almond kernels in response to postharvest moisture exposure. (13th August 2021) - Luo, Kathleen K; Huang, Guangwei; Mitchell, Alyson E
Abstract: BACKGROUND: Almonds are an important crop in California, and increased yields necessitate that dried in‐hull almonds are stored in the field for longer periods, increasing the potential for postharvest moisture exposure (e.g., rain, fog). Processors are increasingly drying these 'wet' almonds to a moisture content of <6% using low heat before the hulling and shelling process in order to reduce mechanical damage to the nutmeat. To date, there is no information on the impact that moisture exposure and drying prior to hulling and shelling has on lipid oxidation and storage shelf life of raw almonds. RESULTS: Raw almonds exposed to ≤8% moisture and subsequently dried (MEx) and almonds not exposed to moisture exposure (≤4% moisture; control) were stored under accelerated shelf life conditions and evaluated monthly over 12 months for free fatty acid (FFA) value, peroxide value (PV), and headspace volatiles. At 12 months of accelerated storage, MEx almonds have 1.4 times higher FFA and 3.5 times higher PV than the control, indicating significant oxidative damage. MEx almonds also demonstrated higher levels of headspace volatile compounds related to lipid oxidation (i.e., hexanal, octanal, hexanoic acid) throughout storage. CONCLUSION: Drying almonds exposed to postharvest moisture prior to storage results in a higher degree of lipid oxidation during storage and a significant reduction in shelf life. © 2021 The Authors. Journal of The Science of Food and Agriculture published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.